2016
DOI: 10.1080/00220671.2016.1169391
|View full text |Cite
|
Sign up to set email alerts
|

Using modeled writing to support English-only and English-learner second-grade students

Abstract: This study compared 70 English learners (ELs) and English-only (EO) second-grade students' writing samples before and after a yearlong writing program. The school utilized Write From the Beginning (J. Buckner, 2006) and focused on personal narratives. A subgroup of students also participated in an intervention supporting expository writing on curricular topics. Sociocognitive theory framed the Modeled Writing (MW) used in this study. An analysis of covariance used prescores on 2 writing assessments to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In a separate study, Hong (2015) found that ESL students evolved from ''others as authors,'' to ''self as an author,'' to ''self as a reflective writer'' (p. 301) and that the process of becoming writers involved different student voices. By comparing the writing of ELL and native English-speaking grade two students, Mohr (2017) found that although students demonstrated good basic writing skills (e.g., spelling, punctuation, logical sentences), the ELLs did not write as much as the native English-speaking students. Studying a grade four Spanish-English bilingual student, Lizette, Wong (2016) found that Lizette's own ideas about writing did not match her teacher's expectations.…”
Section: (B) Approaches Centered On Student Perspectivesmentioning
confidence: 99%
“…In a separate study, Hong (2015) found that ESL students evolved from ''others as authors,'' to ''self as an author,'' to ''self as a reflective writer'' (p. 301) and that the process of becoming writers involved different student voices. By comparing the writing of ELL and native English-speaking grade two students, Mohr (2017) found that although students demonstrated good basic writing skills (e.g., spelling, punctuation, logical sentences), the ELLs did not write as much as the native English-speaking students. Studying a grade four Spanish-English bilingual student, Lizette, Wong (2016) found that Lizette's own ideas about writing did not match her teacher's expectations.…”
Section: (B) Approaches Centered On Student Perspectivesmentioning
confidence: 99%
“…Research has shown that students' L1s were responsible for context-specific challenges for ESL writing instruction. Examples include the role of the first language text production in English and textual characteristics of ESL students in K-2 (Abraham, 2017;Gort, 2012aGort, , 2012bKibler, 2011a;Mohr, 2017;Raynolds & Uhry, 2010). Kibler (2011a) explored teacher-student interactions during a writing task and found that it was challenging for the teacher to recognize and address the unique needs of the Spanish-speaking ESL student whose level of English proficiency was extremely low.…”
Section: Standardized Testsmentioning
confidence: 99%
“…Abraham recognized that teachers in similar contexts should be prepared to do the same. Mohr's (2017) findings suggest that although Grade 2 English learners (EL) demonstrated basic writing skills such as spacing, spelling, capitalization, and punctuation they struggled with descriptive words, closing sentences, transition words, and lead sentences. As well, their writing productivity based on "writing output" and "complexity in expository compositions" (p. 623), was weak, i.e., a score of 3.84 compared with their English-speaking counterparts' 6.18.…”
Section: Standardized Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…It happens because English is as a foreign language not as a second language. Therefore, it is not surprising that for senior high school students, writing in English is difficult task because it needs complex elements (Mohr, 2017). Sometimes changes the components of first-language (L1) into second-language (L2) writing is often as the solution (Kormos, 2012).…”
Section: Introductionmentioning
confidence: 99%